PROFIL LAMA PERSALINAN KALA II BERDASARKAN TINDAKAN AMNIOTOMI DI RSUD 45 KUNINGAN - Dera Sukmanawati; Heri Hermansyah; Nurmalasari Nurmalasari (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2021)
The rupture of the membranes in the presence of a mature cervix and strong contractions never prolong labor. The results of a preliminary study of 30 mothers who experienced rupture of the membranes, 16 of them had a long second stage of labor, and 14 mothers experienced a normal second stage of labor. The aim of the study was to determine the description of the duration of the second stage of labor based on amniotomy at RSUD 45 Kuningan. The research method used was descriptive using partograph sheets in a retrospective way taken from secondary data, the number of samples was 140 respondents, the total sampling technique was the total sampling technique, namely all women who gave birth vaginally at RSUD 45 Kuningan Regency in January-June, analysis data using univariate. The results of the analysis, most of the mothers gave birth at RSUD 45 Kuningan, out of 140 respondents, most of whom did not undergo amniotomy as much as 77.1%. All mothers who did not undergo amniotomy for the duration of the second stage of labor were 100% normal. The results of this study were all women who gave birth who did not undergo amniotomy, the duration of the second stage of labor was normal. It is hoped that health workers will improve the quality and competence of themselves in health services, especially midwives in the delivery room in providing delivery care, especially during the second stage in accordance with midwifery care standards.